2021
DOI: 10.29303/jbt.v21i3.2858
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Test of root, petiole and leaf of Kelembak (Rheum officinale Baill.)

Abstract: Kelembak (Rheum officinale Baill.) is perennial shrub with pharmacological activities, and well-known as one of traditional herbal medicine used widely in the world. The phytochemical study, as well as histochemical test, is pivotal to determine the potency of herbs used for disease treatment. Based on its secondary metabolite content.  Histochemical test of R.officinale vegetative organs had not been reported. This study aims to determine the content of compounds in the vegetative organs of kelembak and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…Several bioactive compounds, such as alkaloids, phenolic compounds, tannins, lipids, and flavonoids, are stored in sponge tissue. 16 The research results show that the more layers of sponges on a leaf, the more potential there is for bioactive compounds such as biolarvacides.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several bioactive compounds, such as alkaloids, phenolic compounds, tannins, lipids, and flavonoids, are stored in sponge tissue. 16 The research results show that the more layers of sponges on a leaf, the more potential there is for bioactive compounds such as biolarvacides.…”
Section: Discussionmentioning
confidence: 97%
“…15 These organelles are abundant in the mesophyll tissue, especially the spongy tissue, which functions as a storage place for metabolic products and by-products. 16 Based on this, it can be that the thicker the spongy tissue of a leaf, the more bioactive compounds it contains. Based on the results of this study, it was found that the potential as a larvicidal bioactive compound of A. alba was superior to that of S. alba.…”
Section: Discussionmentioning
confidence: 99%
“…Uji histokimia dilakukan pada preparat segar nodus dan internodus yang dipotong melintang, serta bunga jantan yang dipotong membujur. Setiap potongan dari nodus, internodus, dan bunga jantan kemudian diuji menggunakan berbagai reagen untuk masingmasing golongan senyawa metabolit sekunder, yaitu fenolik (10% FeCl3 dan larutan Na2CO3), terpenoid (CuSO4 5%), flavonoid (5% NaOH), alkaloid (reagen Dragendoff), tanin (10% FeCl3) (Rahayu dkk., 2021;Mulyani & Laksana, 2011;(Ergina dkk., 2014;Nurhasanah & Iriani, 2021).…”
Section: Pengujian Histokimiaunclassified
“…Plant secondary metabolites are generally accumulated in specialized structures called secretory structures (Lange 2015). Each part of a plant has a different distribution and types of secondary metabolite (Nurhasanah and Iriani 2021;Umar et al 2021a). The anatomical characteristics and secretory structures of medicinal plants need to be validated to ensure authenticity and identify the highest accumulation of a bioactive substance (Coelho et al 2012).…”
Section: Introductionmentioning
confidence: 99%